The embodied performance pedagogy of Jacques Lecoq. Issue 1 (2nd January 2017) - Kemp, Rick
ABSTRACT: This article proposes that acting is a valuable area of research for the fields of Artificial Intelligence and Simulated Behaviour. This suggestion is supported through applying theories and findings from the field of embodied cognition to the performance pedagogy of French acting teacher Jacques Lecoq (1921–1999). Embodied cognition proposes that thinking and behaviour are properties of the whole human organism, not the brain alone, and that body, brain and cognition are "situated" – engaged with the surrounding environment. This thesis arises from findings that show that sensorial and motor experiences form the neural foundations for mental concepts and that sensorimotor neural networks are partially re-activated by mental and linguistic activity, leading to the concept of "embodied simulation". I give examples of the ways in which Lecoq's conceptualisation of acting technique is implicitly congruent with the principles of embodied cognition, and often explicitly anticipates its precepts.